(untitled) (Research, Society and Development, 2022)
Teenage pregnancy is globally recognized as a public health issue. Through an integrative review, this study sought to highlight and discuss the possible consequences of teenage pregnancy. A search was carried out in studies indexed in the databases: Virtual Health Library (VHL), Latin American and Caribbean Literature on Health Sciences (LILACS) and Scientific Electronic Library Online (SciELO), from 2016 to 2021, using The following descriptors (DeCS) are used: contraception, pregnancy complications, teenage pregnancy and teaching. In the end, twelve studies published in Portuguese, Spanish and English were selected. The results showed that, in providing safe information about sexuality, the importance of preventing early pregnancy is linked to family and educational activities, which will result in knowledge about contraception. On the social issue, it is understood that an early pregnancy may impede the continuity of studies and access to the job market, which will accentuate the financial dependence of the parents or partner. Regarding adolescent health, it was found that there is a greater chance of a high-risk pregnancy, which is also one of the major causes of maternal death. There may also be health implications for the baby, such as low birth weight. In this context, the work highlighted the importance of prevention to face the problem in question.